(untitled) (Research, Society and Development, 2021)
Hearing is considered an important sense for insertion in society. The deprivation of this sense can result in the difficulty of using several health services, such as Psychology, considering as possible factors, the professional unpreparedness and the environments that are part of the person daily life. In view of this theme, this article aims to address the challenges encountered in the psychologist’s work in the care of people Qualitative research was carried out, and the method used consisted of a narrative literature review. The results were divided in three categories: equity of care, challenges in health, and psychological assistance to deaf people. In view of professional practice, the difficulty in understanding sign language can present itself as na obstacle in the care of deaf people who are not oralized. Some reasons for this obstacle are related to the lack of theoretical deepening about Libras in undergraduate courses, late learning about this language and the lack of interest in training by professionals. With this study, it is considered the importance of further studies on the subject, since there is a need to support, accept and understand the demands of this audience.